2013
DOI: 10.1097/hp.0b013e318279ba05
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Uranium Concentration in Drinking Water Samples Using ICPMS

Abstract: Uranium concentration in drinking water samples collected from some areas of Northern Rajasthan has been measured using inductively coupled plasma mass spectrometry. The water samples were taken from hand pumps. The uranium concentration in water samples varies from 2.54-133.0 μg L with a mean value of 38.48 μg L. The uranium concentration in most of the drinking water samples exceeds the safe limit (30 μg L) recommended by the World Health Organization. The annual effective dose associated with drinking water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…High radium content in soil samples and uranium content in water samples were reported in Sri Ganganagar district of Rajasthan State by our group (Duggal et al 2013;Rani et al 2013). The aim of the present investigation is to examine the concentration of radon in the soil-gas of Sri Ganganagar district, Rajasthan at different depths and to find a relationship between the soil-gas radon concentration and depth.…”
Section: Introductionmentioning
confidence: 85%
“…High radium content in soil samples and uranium content in water samples were reported in Sri Ganganagar district of Rajasthan State by our group (Duggal et al 2013;Rani et al 2013). The aim of the present investigation is to examine the concentration of radon in the soil-gas of Sri Ganganagar district, Rajasthan at different depths and to find a relationship between the soil-gas radon concentration and depth.…”
Section: Introductionmentioning
confidence: 85%
“…Figure 3 shows the graphical representation of pH, TDS and Conductivity with different locations of Udhampur district. TDS concentrations of water samples are vary from 0.063-0.728 ppt, only 2-3% (Rani et al, 2013), Roper (Singh et al, 2008), and Malwa (Mehra et al, 2007) of Punjab; Kangra of Himachal Pradesh; Fatehbaad , Hisar (Kansal et al, 2011) and Sirsa (Kansal et al, 2011) of Haryana; and Kathua and Jammu (Kumar et al, 2016) districts of Jammu & Kashmir are comparable to present work and Lower than Amritsar (Rani et al, 2013), Bathinda (Bajwa et al, 2015), Andrah Pradesh (Brindha and Elango, 2013), and Western Haryana (Singh et al, 2014) as shown in Table 4. The reported values were also compared with worldwide as shown in Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…10 (Kumar et al, 2016) to remove suspended particle and is transferred to 50 mL polyethylene plastic bottles previously cleaned with distilled water. The fluorimetric method for Uranium is among the most sensitive and efficient, of detection limit 0.5 mg L À1 to 1000 mg L À1 with an accuracy of ±10% or 0.05 mg L À1 whichever is greater and repeatability is better than ±5% (Kumar et al, 2016) and in ICP-MS, the precisions achieved were ±5% relative standard deviation (RSD) with comparable levels of accuracy (Rani et al, 2013). Uranium concentration of collected samples was calculated by LED-Flourimeter (Quantalase Enterprise Pvt.…”
Section: Estimation Of Uranium Concentration-led Flourimetermentioning
confidence: 99%
See 1 more Smart Citation
“…The uranium concentration in Hanuman Garh district varies from 4.74 to 98.7 µg/L and Shri Ganga Nagar District from 4.42 to 133.0 µg/L, Churu district from 10.75 to 81.3 µg/L and Sikar district varied from 2.54 to 28.38 µg/L used inductively coupled plasma mass spectrometry (ICPMS) for the measurement of uranium in water [20]. Parameters for radiological effect of uranium such as annual effective dose, commutative dose and life time stochastic health effect in Rajasthan was within safe limit [20].…”
Section: Summary Of the Studies Conducted In North Indiamentioning
confidence: 99%